The Role of the Complement System in Chronic Intestinal Inflammation - mohamed, fatima (The Libyan Journal of Science, 2024)
Complement is an important component of the innate immunity that can initiate or sustain inflammation but can modulate the developing adaptive immune response against invading foreign pathogens. Chronic inflammation is a characteristic of many long-term clinical disorders. An imbalance in the activation and regulation of the intestinal complement system hampers effective intestinal barrier function and hence contributes to severe intestinal inflammation as observed in inflammatory bowel diseases patients. Animal models have been instrumental in the evaluation of over-activation or impaired activation of the intestinal complement system in determining the extent of chronic intestinal inflammation. This review examines the role and possible therapeutic manipulation of complement system in chronic intestinal inflammation.